Evaluating a large language model’s ability to answer clinicians’ requests for evidence summaries - Mallory N. Blasingame; Taneya Y. Koonce; Annette M. Williams; Dario A. Giuse; Jing Su; Poppy A. Krump; Nunzia Bettinsoli Giuse (Journal of the Medical Library Association)
Objective: This study investigated the performance of a generative artificial intelligence (AI) tool using GPT-4 in answering clinical questions in comparison with medical librarians’ gold-standard evidence syntheses.